The Republic of Guinea and Ebola hemorrhagic fever outbreak - Camara, Ansoumane Yassima; Diallo, Lansana Laho; Camara, Moussa Kantara; Kouyate, Moustapha; Keita, Sadio; Diawara, Safere; Camara, Mohamed ElMady; Traore, Falaye (International Journal Of Community Medicine And Public Health, 2017)
Background: The authors analysed the Ebola Virus Disease (EVD) outbreak in Guinea. They summarised the epidemic impact on the country’s health care system, its economy, education, domestic policies and its international cooperation. Methods:This was a descriptive study based on statistics, published by the World Health Organization (WHO) in the Ebola Situation Reports in response to the Ebola Hemorrhagic Fever (EHF) outbreak in West Africa. Results: It was found that of November 21st 2015, Guinea had 3351 confirmed cases of EVD and 453 probable cases, the disease had claimed the life of 2536 people with a fatality rate of 66.6%. The epidemic had an important impact on the country’s economy, education, domestic policies and international cooperation. Conclusions:The EVD outbreak in Guinea was one of the longest Ebola outbreaks in the world. It pointed out the weakness of the Guinean health system. This should be an opportunity to ensure that the country’s health system is strengthened. A robust surveillance measure to ensure the rapid detection of any reintroduction or re-emergence of EVD or other diseases of obligatory declaration should be reinforced.